2018
DOI: 10.1101/394445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental DNA for the enumeration and management of Pacific salmon

Abstract: Pacific salmon are a keystone resource in Alaska, with an economic impact of well over

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 27 publications
3
76
0
Order By: Relevance
“…eDNA concentrations varied substantially from near zero to a high of 328,000 copies/μl during the peak of the run in 2017. The product of streamflow and eDNA concentration, which we refer to as "flow-corrected eDNA rate" (Figure 3, see also Levi et al, 2019), was highly predictive of the eulachon population estimate generated through the mark-recapture method. The natural log of the eDNA peak was significantly related to, and explained 84.…”
Section: Environmental Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…eDNA concentrations varied substantially from near zero to a high of 328,000 copies/μl during the peak of the run in 2017. The product of streamflow and eDNA concentration, which we refer to as "flow-corrected eDNA rate" (Figure 3, see also Levi et al, 2019), was highly predictive of the eulachon population estimate generated through the mark-recapture method. The natural log of the eDNA peak was significantly related to, and explained 84.…”
Section: Environmental Dnamentioning
confidence: 99%
“…While the environmental DNA shed from an organism is now widely used for species detection in a wide variety of contexts (Barnes & Turner, 2016;Jerde, Mahon, Chadderton, & Lodge, 2011;Laramie, Pilliod, & Goldberg, 2015;Mächler, Deiner, Steinmann, & Altermatt, 2014;Rees, Maddison, Middleditch, Patmore, & Gough, 2014;Takahara, Minamoto, Yamanaka, Doi, & Kawabata, 2012), mobilizing environmental DNA for management requires estimation of population size and trends in addition to assessing presence or absence. Recent research suggests that eDNA quantified with real-time quantitative polymerase chain reaction (PCR) or digital-droplet PCR can provide a proxy for actual abundance in controlled experiments (Rees et al, 2014), in ponds (Lacoursière-Roussel, Côté, Leclerc, & Bernatchez, 2016;Takahara et al, 2012) in streams (Doi et al, 2015;Levi et al, 2019;Lodge et al, 2012;Tillotson et al, 2018;Wilcox et al, 2016) and in marine bays (Plough et al, 2018). However, the efficacy of environmental DNA based indices of abundance in natural settings have produced mixed results (Yates, Fraser, & Derry, 2019) and have not yet been assessed in a management context for long-term population monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some previous studies have not found read depth for species biodiversity to correlate with individuals, biomass, or density [59,[100][101][102]. However, a more recent study indicates strong evidence that flow-corrected eDNA abundance reflects salmon count abundance in two species across two years and life stages [103]. Relating allelic abundance to eDNA genetic variation is necessary to understand allelic frequency differences between and within populations.…”
Section: Challenges Facing Environmental Dna Population Geneticsmentioning
confidence: 99%
“…Other ways to get at quantification of allelic copy number include a correction factor depending on cell type, size, life-history stage and species, which could be integrated into single-cell methodology [104]. Lastly, the more that is understood about the ecology of eDNA in a field setting, the better we can understand and model eDNA abundance [103,141].…”
Section: Further Developments and Future Technologiesmentioning
confidence: 99%
“…quantity of eDNA may be related not only to species presence, but also to abundance 16,21,[28][29][30][31][32] . Although promising as a method for shark detection, more research in well-studied ecosystems is necessary to understand whether eDNA monitoring can also be used to track population dynamics over time.…”
mentioning
confidence: 99%